A 10-year-old Boy with Microscopic Hematuria and Renal Biopsy Findings Mimicking Fabry Disease - Woo Yeong Chung; Mi Seon Kang (Korean Society of Pediatric Nephrology, 2016)
Fabry disease is an X-linked lysosomal storage disorder caused by a deficiency of the enzyme α-galactosidase A, resulting in the accumulation of glycosphingolipids within the lysosomes of various cell types. It has a wide spectrum of clinical phenotypes, and renal failure is a serious complication. Fabry disease is confirmed either by measurement of α-galactosidase A activity or by genetic testing for GLA mutations. Renal biopsy findings on light microscopy, specifically enlarged podocytes with foamy cytoplasm, and osmiophilic inclusion bodies in the cytoplasm in all types of renal cells on electron microscopy, are characteristic of this disease. The predominant differential diagnosis is iatrogenic phospholipidosis in association with certain drugs that can cause cellular injuries indistinguishable from Fabry disease. Here, we report the case of a 10-year-old boy with microscopic hematuria who underwent a renal biopsy that showed morphological findings consistent with Fabry disease, although the patient had neither a GLA mutation nor a history of drug consumption. Six years later, spontaneous regression of this renal pathology was observed in a second renal biopsy examination.